2019
DOI: 10.1101/783464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

P2X1 selective antagonists block HIV-1 infection through inhibition of envelope conformation-dependent fusion

Abstract: word count: 350 35 Text word count: 6244 36 37 38 39 3 Abstract 40 41 Purinergic receptors detect extracellular ATP and promote inflammatory processes. Emerging literature 42has demonstrated that inhibition of these proinflammatory receptors can block HIV-1 productive infection. The 43 specificity of receptor type and mechanism of interaction has not yet been determined. Here we characterize 44 the inhibitory activity of P2X1 receptor antagonists, NF279 and NF449 in cell lines, primary cells, and in a 45 varie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Numerous studies describe the role of purinergic receptors and their antagonists at various stages of the viral life cycle and downstream impacts on pathogenesis. In the following section, we will review the literature as it pertains to the role of purinergic receptors and their antagonists on HIV- P2X7R and P2YR antagonists have been shown to inhibit HIV-1 infection at potencies similar to those of P2X1R antagonists (94,97,(116)(117)(118)(119), but these compounds do not appear to impact virus-cell membrane fusion. The P2X7R antagonist A740003, which inhibits HIV-1 infection (94), fails to inhibit virus-membrane fusion as measured by BlaM-Vpr assays (94,114,118).…”
Section: Purinergic Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies describe the role of purinergic receptors and their antagonists at various stages of the viral life cycle and downstream impacts on pathogenesis. In the following section, we will review the literature as it pertains to the role of purinergic receptors and their antagonists on HIV- P2X7R and P2YR antagonists have been shown to inhibit HIV-1 infection at potencies similar to those of P2X1R antagonists (94,97,(116)(117)(118)(119), but these compounds do not appear to impact virus-cell membrane fusion. The P2X7R antagonist A740003, which inhibits HIV-1 infection (94), fails to inhibit virus-membrane fusion as measured by BlaM-Vpr assays (94,114,118).…”
Section: Purinergic Receptorsmentioning
confidence: 99%
“…The same assay demonstrated that the broad-spectrum P2 receptor inhibitor PPADS likewise has no effect on virus-membrane fusion, Our laboratory additionally demonstrated that NF449 and NF279-mediated fusion inhibition relies on intact gp41 and displays varied activity against diverse clades. The inhibitory activity of NF279 and NF449 appeared to interfere specifically with Env, as NF279 and NF449 inhibited viral membrane fusion and impacted PG9 antibody accessibility, which targets the V1V2 region of HIV-1 gp120 (119).…”
Section: Purinergic Receptorsmentioning
confidence: 99%